2009
DOI: 10.1016/j.ygyno.2009.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Extragenital adenosarcoma: A case report, review of the literature, and management discussion

Abstract: Background Müllerian adenosarcoma is a rare mixed epithelial-mesenchymal tumor. An extragenital site of origin and sarcomatous overgrowth are associated with aggressive clinical behavior. Case We present a rare case of extragenital adenosarcoma with sarcomatous overgrowth and coexistent endometrioisis. She was treated with initial cytoreductive surgery and chemotherapy. She underwent a second surgery for management of a high-grade bowel obstruction, due to pathologically confirmed recurrent intraperitoneal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…14 Alternatives include a combination of ifosfamide and cisplatin, or gemcitabine with docetaxel. 7 Adjuvant therapy with aromatase inhibitors has also been described. 15 Adjuvant radiotherapy may be included as part of a combined regimen if there is an increased recurrence risk, although there is a paucity of evidence for this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Alternatives include a combination of ifosfamide and cisplatin, or gemcitabine with docetaxel. 7 Adjuvant therapy with aromatase inhibitors has also been described. 15 Adjuvant radiotherapy may be included as part of a combined regimen if there is an increased recurrence risk, although there is a paucity of evidence for this.…”
Section: Discussionmentioning
confidence: 99%
“…This aggressive behavior may be explained by the tumor's free access to the peritoneal cavity, with transcoelomic spread not hampered by the myometrium, compared to an uterine adenosarcoma. 7 A poorer prognosis may also be attributable to the increased risk of local complications at extrauterine sites, such as bowel obstruction; later presentation and, therefore, more advanced disease at diagnosis; and greater difficulty in achieving complete surgical clearance. 6,17 Second, the absence of underlying endometriosis confers a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematogenous metastases occur in 33% of extragenital cases compared with 2% of uterine primaries. Mortality rates are 40% and 10% in extrauterine and (8) uterine adenosarcomas, respectively (8)(9)(10). The reasons for the poorer prognosis of extragenital adenosarcoma have not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Huang et al (10) suggested that the presence of endometriosis might confer a better prognosis in patients with extragenital adenosarcoma. Extragenital adenosarcoma may develop from malignant transformation of endometriosis or originate from multipotential pelvic mesothelial cells (7).…”
Section: Discussionmentioning
confidence: 99%